ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN PARKIR DI RUMAH SAKIT BAHTERAMAS PROV. SULAWESI TENGGARA - Muhammad Ridwan Safar; Baso Mursidi; Fitriah Mas'ud (PRODI D3 TEKNIK SIPIL, 2017)
Abstract Measurement of the quality of parking services need to be done to increase the quality of service. On this occasion the author took a case study of parking attendants at Bahteramas Prov. Southeast Sulawesi. The purpose of this study is to determine the importance of each attribute based on the method of Importance Performance Analysis (IPA) and to know the level of customer satisfaction based on Customer Satisfaction Index (CSI) method.From the IPA analysis the attributes are the main priority (first quadrant) are Ease of parking of the vehicle, the parking officer gives the right information, and the parking officer Provides prompt and prompt service. Based on the research that has been done, it can be concluded that the level of satisfaction of parking service in Bahteramas Hospital Prov. Southeast Sulawesi has the title